Serum diamine oxidase levels in allergic asthma and/or allergic rhinitis - Ilkay Keskinel; Muzeyyen Eryilmaz; Asuman Akkaya Firat (Medicine, 2026)
Histamine is a central mediator in immunoglobulin E (IgE)-mediated allergic responses, and diamine oxidase (DAO) contributes to extracellular histamine degradation. Altered histamine metabolism has been proposed as a potential modifier of symptom burden in atopic conditions. However, whether circulating DAO protein concentrations differ in patients with allergic asthma and/or allergic rhinitis remains unclear. This study aimed to compare serum DAO concentrations between patients with allergic asthma and/or allergic rhinitis and healthy controls and to examine their associations with immunological and respiratory parameters. In this cross-sectional study, 141 patients with allergic asthma and/or allergic rhinitis and 78 healthy controls were enrolled between January 1, 2025, and March 1, 2025. Serum DAO protein concentrations were measured using enzyme-linked immunosorbent assay. Additional assessments included total IgE, eosinophil count, eosinophil cationic protein, and spirometric parameters. Statistical analyses comprised group comparisons, Spearman's correlation analysis, and receiver operating characteristic curve analysis. Median serum DAO concentrations were significantly lower in patients with allergic asthma and/or allergic rhinitis than in healthy controls (13.8 U/mL vs 28.2 U/mL; P < .001). DAO levels were not significantly correlated with age, sex, total IgE, eosinophil indices, eosinophil cationic protein, or pulmonary function parameters. Receiver operating characteristic analysis demonstrated good discriminatory performance (area under the curve = 0.84, 95% confidence interval = 0.79–0.89; P < .001). The optimal cut-off value of 22.2 U/mL yielded 80% sensitivity and 87% specificity, although this threshold requires external validation. Circulating DAO protein concentrations were reduced in patients with allergic asthma and/or allergic rhinitis compared with healthy individuals. Given the cross-sectional design and the lack of direct enzymatic activity assessment, the results should be interpreted as hypothesis-generating. Prospective studies are warranted to clarify the clinical relevance of DAO measurement in allergic diseases.